Prevalence and Predictors of Insulin Resistance in Overweight and Obese Children and Adolescents: A Hospital-based Study - Kutbi, Hebah; Al Agha, Abdulmoein (Progress in Nutrition, 2022)
Background/Aim: To estimate the prevalence and predictors of insulin resistance (IR) among overweight and obese children and adolescents.Material and Methods: Data of this cross-sectional study included 62 overweight and obese children and adolescents (8-19 years of age), who visited the pediatric endocrinology clinic of King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Participants’ sociodemographic and health characteristics, dietary habits, physical activity, anthropometric measurements, and values of homeostasis model assessment of insulin resistance (HOMA-IR) were evaluated. Multiple regression analyses were conducted with [95% confidence intervals].Results: Among our sample, 59.7% of the participants (n=37) were insulin resistant. Among the evaluated predictors, physical activity and waist circumference (WC) predicted the risk for IR (B=-0.218 [-0.410 to -0.26] and B=0.127 [0.001, 0.016], respectively). Examining the associations between HOMA-IR values and anthropometric measurements while stratifying by maternal educational status revealed that the associations between WC and waist-hip ratio with IR were mediated by maternal educational status, and those associations were only observed in children of less educated mothers (B=0.014 [0.004, 0.024] and B=2.156 [0.635, 3.676], respectively).Conclusion: High prevalence of IR was observed among our sample. Future studies are needed to investigate the nationwide prevalence and predictors of IR among overweight and obese children and adolescents. Special attention should be paid to children of low-educated mothers for early detection and management.